2008
DOI: 10.4137/cin.s802
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-tumour Agent, Cisplatin, and its Clinically Ineffective Isomer, Transplatin, Produce Unique Gene Expression Profiles in Human Cells

Abstract: Cisplatin is a DNA-damaging anti-cancer agent that is widely used to treat a range of tumour types. Despite its clinical success, cisplatin treatment is still associated with a number of dose-limiting toxic side effects. The purpose of this study was to clarify the molecular events that are important in the anti-tumour activity of cisplatin, using gene expression profiling techniques. Currently, our incomplete understanding of this drug’s mechanism of action hinders the development of more efficient and less h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 153 publications
(186 reference statements)
0
6
0
Order By: Relevance
“…However, because of the same action mechanism as CDDP, there was no great breakthrough on the improvement of toxicity and side effects. Trans-diamminedichloroplatinum (II) (TDDP), the trans-isomer of CDDP, was previously known to be ineffective [5,6]. Due to the different structures of cis-and trans-platinum complexes, they produced different action mechanisms with DNA and in turn led to different biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the same action mechanism as CDDP, there was no great breakthrough on the improvement of toxicity and side effects. Trans-diamminedichloroplatinum (II) (TDDP), the trans-isomer of CDDP, was previously known to be ineffective [5,6]. Due to the different structures of cis-and trans-platinum complexes, they produced different action mechanisms with DNA and in turn led to different biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Inaccurate measures can also be a consequence of drug isomerism [ 28 , 29 ]. In the case of cisplatin, trans-isomerization impairs its clinical efficacy [ 30 ], while isomerization of cetirizine to levocetirizine [ 28 ] led to the development of a safer and more effective drug alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin, cis- [Pt­(NH 3 ) 2 Cl 2 ] (CDDP), and its platinum derivatives are still the most frequently used transition metal complexes in the treatment of various cancer types . However, the corresponding trans isomer, transplatin (t rans -[(NH 3 ) 2 Cl 2 Pt]), remains therapeutically inactive. , It has been suggested that the orientation of the cis chlorides is key for therapeutic activity, whereby CDDP forms ∼80% of intrastrand DNA cross-links, while transplatin forms monoadducts and interstrand DNA cross-links. In 2019 Quiroga et al reported a series of aliphatic amine Pt­(II) complexes and highlighted the cis dichlorido complexes have similar modes of action to cisplatin, while the trans diiodido complexes exhibit different modes of action and activate the cytoplasmic protein BID, suggesting a pro-apoptotic cascade. , Generally, Pt-based therapeutics have poor cancer cell selectivity, which is associated with many adverse side-effects and has led chemotherapy research toward new non Pt-based alternatives such as Ru, Os, Rh, and Ir complexes, in an attempt to overcome some of these selectivity issues. In particular, organometallic complexes have been prominent, with many compounds exhibiting high potency toward cancerous cells, while remaining nontoxic toward normal cell types, allowing for a more targeted therapy and reduction in patient side effects …”
Section: Introductionmentioning
confidence: 99%